Drug-Loaded Zein Nanofibers Prepared Using a Modified Coaxial Electrospinning Process - Huang, Weidong (Springer US, 2013)
This study investigated the preparation of drug-loaded fibers using a modified coaxial electrospinning process, in which only unspinnable solvent was used as sheath fluid. With zein/ibuprofen (IBU) co-dissolving solution and N, N-dimethylformamide as core and sheath fluids, respectively, the drug-loaded zein fibers could be generated continuously and smoothly without any clogging of the spinneret. Field emission scanning electron microscopy and transmission electron microscopy observations demonstrated that the fibers had ribbon morphology with a smooth surface. Their average diameters were 0.94 ± 0.34 and 0.67 ± 0.21 μm when the sheath-to-core flow rate ratios were taken as 0.11 and 0.25, respectively. X-ray diffraction and differential scanning calorimetry verified that IBU was in an amorphous state in all fiber composites. Fourier transform infrared spectra showed that zein had good compatibility with IBU owing to hydrogen bonding. In vitro dissolution tests showed that all the fibers could provide sustained drug release files via a typical Fickian diffusion mechanism. The modified coaxial electrospinning process reported here can expand the capability of electrospinning in generating fibers and provides a new manner for developing novel drug delivery systems.